2001
DOI: 10.1111/j.1530-0277.2001.tb02354.x
|View full text |Cite
|
Sign up to set email alerts
|

Divalproex Sodium in Alcohol Withdrawal: A Randomized Double‐Blind Placebo‐Controlled Clinical Trial

Abstract: This placebo-controlled pilot study suggests that divalproex sodium significantly affects the course of acute alcohol withdrawal and reduces the need for treatment with a benzodiazepine. A more aggressive loading dose strategy may demonstrate a more robust or earlier response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(28 citation statements)
references
References 23 publications
(16 reference statements)
3
23
0
2
Order By: Relevance
“…During the study, participants treated with zonisamide had less craving for alcohol, less anxiety, and less daytime sedation compared with participants treated with diazepam. Similar results have been reported in comparative studies between benzodiazepines (oxazepam, lorazepam) and anticonvulsants [5,13,14,17,35] . In another study with a similar design performed by our team, oxcarbazepine was found to have a similar effi cacy to diazepam in the prevention of epileptic seizures during alcohol detoxifi cation [19] .…”
Section: Outcomes During the Outpatient Period (Week 3)supporting
confidence: 86%
“…During the study, participants treated with zonisamide had less craving for alcohol, less anxiety, and less daytime sedation compared with participants treated with diazepam. Similar results have been reported in comparative studies between benzodiazepines (oxazepam, lorazepam) and anticonvulsants [5,13,14,17,35] . In another study with a similar design performed by our team, oxcarbazepine was found to have a similar effi cacy to diazepam in the prevention of epileptic seizures during alcohol detoxifi cation [19] .…”
Section: Outcomes During the Outpatient Period (Week 3)supporting
confidence: 86%
“…In Kenya, Diazepam is commonly used. The use of anticonvulsants as a treatment for acute alcohol withdrawal has been investigated in several studies [31][32][33][34][35], as well as considered in two meta-analyses [36,37] and a review [38], and has been reported to be an effective agent during the period of detoxification.…”
Section: Introductionmentioning
confidence: 99%
“…While benzodiazepines and barbiturates have been the primary treatment modality for alcohol withdrawal, 1,2 a growing number of clinical studies suggests that the anticonvulsants represent desirable alternatives 3–13 . Benzodiazepines and barbiturates have the disadvantages of respiratory depression, potential for drug‐drug interactions, and their own dependence liability.…”
mentioning
confidence: 73%